Hi-Tech-Oriented National Service: The Free Choice of Religious Women Recruits and the De-Monopolization of the Israeli Military - Itamar Rickover (MDPI AG, 2021)
In recent years, Israel has witnessed two significant processes that challenge the dominant republican discourse that prioritizes military over national-civic service (known as The Israeli national-civilian service—NCS)in terms of contributing the constitution of citizenship and of the material and symbolic convertibility offered to service candidates. The first is related to the expanding range of roles offered in the NCS. The second, related process, which is our current focus, occurs among young religious women from the urban upper-middle class who respond to this expansion by seeking to serve in technological roles, given their high qualifications. Combined, these processes transform the status of the NCS and accelerate the de-monopolization of military service. To examine the contribution of religious young women to the change in the status of service in Israel, we conducted a narrative analysis of interviews with service candidates. Our analysis revealed their strategic use of four different discourses: the neo-liberal economic discourse, the liberal rights and self-realization discourse, the ethnonational discourse, and the religious gender discourse. The way the participants negotiated the four discourses to justify their selection of either military or national-civic service structured their agency as actors transforming the power equation between the two types of service.